Predictive value of neutrophil percentage-to-albumin ratio for contrast-associated acute kidney injury in patients without chronic kidney disease undergoing elective percutaneous coronary intervention. (14th October 2021) - He, H; Lin, X; Luo, M; He, C; Zhang, S; Lin, M; Lin, K; Guo, Y
Abstract: Background: Although previous studies have demonstrated that neutrophil and albumin are biomarkers of inflammation and malnutrition, which are highly related with contrast-associated acute kidney injury (CA-AKI). However, there has been no study investigated the combined evaluation of neutrophil and albumin in predicting CA-AKI. Purpose: To explore the predictive value of neutrophil percentage-to-albumin ratio (NPAR) for CA-AKI in patients undergoing elective percutaneous coronary intervention (PCI). Methods: We prospectively observed 5083 consenting patients without chronic kidney disease (CKD) undergoing elective PCI from January 2012 to December 2018. NPAR was calculated as neutrophil percentage numerator divided by serum albumin concentration. CA-AKI was defined as an increase in serum creatinine (SCr) ≥50% or 0.3 mg/dL within 48 hours after contrast medium exposure. The association between NPAR and CA-AKI was investigated by logistic regression analysis. The area under the receiver-operating characteristic curve (AUC), continuous net reclassification improvement (NRI), and integrated discrimination improvement (IDI) were calculated to make comparison for CA-AKI prediction. Result: The incidence of CA-AKI was 5.6% (n=286). The median NPAR was 14.9 (13.0–17.1). According to the receiver operating characteristic curves (ROC), the best cut-off value of NPAR for predicting CA-AKI was 15.7 with 66.8% sensitivity and 61.9% specificity (C statistic=0.679; 95% CI, 0.666–0.691). NPAR displayed higher AUC value in comparison to neutrophil percentage (p<0.001), but not albumin (P=0.063), as a predictor of CA-AKI. However, NPAR significantly improved the prediction of CA-AKI in the continuous NRI and IDI over neutrophil percentage (NRI: 0.353, 95% CI: 0.234–0.472, P<0.001; IDI: 0.017, 95% CI: 0.010–0.024, p<0.001) and albumin (NRI: 0.141, 95% CI: 0.022–0.260, P=0.020; IDI: 0.009, 95% CI: 0.003–0.015, p=0.003) alone. After adjusting for potential confounding risk factors of CA-AKI, multivariable logistic analysis showed that NPAR >15.7 was a strong independent predictor of CA-AKI (OR=1.998, 95% CI, 1.511–2.643, p<0.001). Conclusion: NPAR is an independent predictor of CA-AKI, which significantly improved the prediction of CA-AKI over neutrophil and albumin alone in patients without CKD undergoing elective PCI. Funding Acknowledgement: Type of funding sources: None.